A new, higher yielding synthetic route towards dodecaphenyl cage silsesquioxanes: synthesis and mechanistic insights - Lee, Albert S.; Choi, Seung-Sock; Lee, He Seung; Baek, Kyung-Youl; Hwang, Seung Sang (ROYAL SOC CHEMISTRY, 2012)
Cage dodecaphenylsilsesquioxane (T12-Phenyl) was synthesized in a one batch, mildly basic aqueous solution under room temperature conditions using a trialkoxysilane precursor. Significant improvements in synthetic yield (>95%) were observed compared with previous reports. Kinetic studies of the hydrolysis of phenyltrimethoxysilane were conducted and the condensation was monitored by Si-29 NMR which revealed the presence of a transient, intermediary T1 species as the pathway to dodecaphenylsilsesquioxane spherulites, and the tendency for T12 structures over T8, T10, and other substructures was explained through MM2 simulations.
Keywords: POLYHEDRAL OLIGOMERIC SILSESQUIOXANES; SUBSTITUTED POSS; PHENYLSILSESQUIOXANES; PROPERTY; POLYMERS; T-8